Qualidade de Vida em Mulheres Profissionais das Unidades Básicas de Saúde de São João do Triunfo – PR - Woicolesco, Thailine Ellen Chimin (2018)
To characterize the indicators of Quality of Life according to sociodemographic, health - related and behavioral variables in professional women who work in the Basic Health Units in São João do Triunfo - PR. Methods: Cross-sectional, quantitative, ex post facto study. Descriptive statistics of the variables were performed and, to identify the factors associated with the Quality of Life of female professionals, Linear Regression models were constructed in univariate and multivariate models, which were estimated by points and intervals with 95% confidence. The variables for which they obtained values p <0.25 (Wald test) were candidates for multivariate models. In the final multivariate models, the variables that presented p values <0.05 remained. Results: The sample consisted of the prevalence of single women (74.19%), the mean age was 35.11 years, and overweight and obesity (58.06%). In relation to the practice of physical activity, the prevalence in the condition was sufficiently active with 78.52%. The professionals showed greater satisfaction with Quality of Life related to the Physical Domain (73.91%), and greater dissatisfaction with the Environmental Domain (65.52%), and 69.34% of them are satisfied with their Quality of Life. The main variables associated to the Domains were self-rated health, marital status and physical activity practice. Final considerations: The main factors that negatively influence the Quality of Life of the professionals surveyed are lack of recreational and leisure opportunities, lack of financial resources, smoking and overweight / obesity. And factors such as the practice of physical activity, mobility and little dependence on medication or treatments, were associated with better perception of Quality of Life, and the incentive to these conditions is essential.